An update on the distribution of yellow-throated marten Martes flavigula in Nepal - Basnet, Hari; Rai, Anu (Nepalese Journal of Zoology, 2020)
The yellow-throated marten Martes flavigula is encountered frequently by many researchers or nature guides but the information remains unavailable to the wider scientific community. The conservation efforts are already stretched thin and the species being Least Concern in the IUCN Red List of Threatened Species points to the reality that a dedicated budget for studying its ecology and distribution will not be readily available. We try to amend this data gap by presenting a non-targeted survey of the yellow-throated marten from May 2013 to January 2020 recorded during the field work in the mid hills and mountains of Nepal. The species was reported from 22 different sites which includes five protected areas of Nepal. Among them, we reported the species for the first time from Dhorpatan Hunting Reserve and districts of Achham, Bajura and Gulmi. We recommend a guideline to be developed for recording the opportunistic sightings and encourage researchers to share their records that will improve understanding of yellow-throated marten distribution in Nepal.